2014
DOI: 10.1007/s40279-014-0297-0
|View full text |Cite
|
Sign up to set email alerts
|

Half-Time Strategies to Enhance Second-Half Performance in Team-Sports Players: A Review and Recommendations

Abstract: A number of intermittent team sports require that two consecutive periods of play (lasting for ~30-45 min) are separated by a 10-20 min half-time break. The half-time practices employed by team-sports players generally include returning to the changing rooms, temporarily relaxing from the cognitive and physical demands of the first half, rehydration and re-fuelling strategies, addressing injury or equipment concerns, and receiving tactical instruction and coach feedback. However, the typically passive nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 82 publications
2
73
0
2
Order By: Relevance
“…Therefore, the efficacy of intervention strategies administered over HT also warrants further investigation. 28 Temporal match-related fatigue development is a complex phenomenon, with a multitude of putative factors, 7 including depletion of endogenous fuel stores, 8 compromised excitationcontraction coupling 7 and dehydration. 29 Logistical constraints prevented the assessment of each of these factors in isolation in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the efficacy of intervention strategies administered over HT also warrants further investigation. 28 Temporal match-related fatigue development is a complex phenomenon, with a multitude of putative factors, 7 including depletion of endogenous fuel stores, 8 compromised excitationcontraction coupling 7 and dehydration. 29 Logistical constraints prevented the assessment of each of these factors in isolation in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a re‐warm‐up phase including five‐repetition leg‐press exercise was shown to improve subsequent RS performance during an intermittent team‐sport activity (Zois et al., ). While “passive” heat maintenance strategies are potentially beneficial in preparing some athletes (e.g., between warm‐up end and competition heat in sprinters) for short‐term “sprint”‐based activities (i.e., greater preservation of temperature‐related warm‐up mechanisms), such practices should however be carefully controlled with others (e.g., tennis players who may compete for several hours) so as not to become counterproductive in situations of elevated heat stress (Russel et al., ). Practically, it may be more efficient for team‐sport players to cool down during breaks into competition, for instance, during halftime in footballers, so that in the long term sprint performance will be better maintained for the entire second half.…”
Section: Implications For Real‐world Settingsmentioning
confidence: 99%
“…Taking this in consideration, the effectiveness of a WU also relies on the re-warm up (R-WU) activities implemented during the period between the end of the WU and the start of competition. However, few studies have examined the effects of specific post-activation activities on footballers and have exclusively focused on the R-WU during half-time [4]. These have shown that passive half-times appear to impair sprint and jump performance during the initial phase of the second half whereas R-WU effectively attenuates such deteriorations [5].…”
Section: Introductionmentioning
confidence: 99%
“…Champions League), teams’ presentation and official anthems imply that players may passively rest for approximately 15 minutes before the match. As a result, the WU short-term effects that are highly dependent on alterations in muscle temperature may be lost [4]. In fact, it was already demonstrated that every 1°C reduction in muscle temperature corresponded to a 3% reduction in lower-body power output [6].…”
Section: Introductionmentioning
confidence: 99%